Editing Cross Cutting Untuk Mendukung Pola Penceritaan Non-Linear Pada Film Inception (2010) - Luthfi, Muhammad; Haryanto, Dwi; Suharto (Universitas Jember, 2025)
Cross cutting is one of the editing techniques in the film world that plays a role in supporting non-linear storytelling patterns. This technique allows simultaneous and dynamic movement between space and time, providing a complex and captivating narrative experience for the audience. This article aims to analyze the use of cross cutting editing in supporting non-linear storytelling patterns in Christopher Nolan's film Inception (2010). Through a descriptive qualitative research method, this study explores how the arrangement of rhythm, continuity, and manipulation of time flow through cross cutting can create layers of stories that are logically and emotionally connected. The results of the study show that cross cutting not only functions as a transition tool between scenes, but also becomes a narrative element that strengthens the theme and the audience's understanding of the complex storyline.